Impact load bearing and energy absorption in sandwich polymer composites: Projectile versus shock loadings - G. Sakthi Balan; S. Aravind Raj (Results in Engineering)
Two modalities of impact force application were utilized in this study: low velocity impact caused by a hemispherical projectile and shock wave. By utilizing a shock tube to generate the high-pressure shock waves, the sandwich composite panels were induced to interact with the shock waves. During both categories of impacts, the energy absorption capacities and corresponding deformations of the composite panels were assessed. Regression analyses were conducted in order to identify the most significant factor that influences the responses. The novelty of this study is the core design, which incorporates glass fiber and steel wire meshes between the core and the face sheets. For the first time, sandwich composites have been tested under shock load circumstances, and their deformation behavior has been examined. The findings indicated that the incorporation of wire meshes made with glass fiber and steel improves the energy absorption of the sandwich composites while causing the least amount of deformation. Additionally, the severity of post-impact deformations is influenced by the type of face sheet joining method. Notably, the performance of the composites improved when exposed to shock wave impact within a closed shock tube. The analysis of X-ray diffraction revealed that the shock wave impact caused structural and crystallinity changes in the core material. The drop weight test yielded maximum energy absorption of 108.73 Joules, while the composite specimens exhibited a maximum deformation of 0.38 mm subsequent to the shock impact.